Rancang Bangun Body Fibercarbon dan Simulasi Aerodinamis dengan Ansys untuk Mobil Hemat Energi Kategori Prototype - Yusuf Eko Nurcahyo; Pongky Lobas Wahyudi (Proklamasi 45 University, 2021)
Body is one of mandatory components for the main vehicle, which is a car because the face of the car is located on the body. Moreover, the car used for the body competition must not only be good visually but also have to look at its aerodynamics. In this study, discussing the aerodynamics of a prototype energy-efficient car body with carbon fiber material before it is produced and applied it must first be simulated aerodynamically on an aerodynamic simulation software. The vehicle to be simulated uses a 1:1 scale assuming the actual conditions. From the simulations carried out by the three body type models, the results are Model 1 with maximum Velocity of 64.0925 m/s and a maximum pressure of 1663.09 Pa and a Drag coefficient of: 309.85976, Lift coefficient of: 125.52961, Drag force of : 189.7891 N and Lift force of: 76.886889 N. Model 2 with a maximum Velocity of 58.14 m/s and a maximum pressure of 1350.55 Pa, Drag coefficient of : 399.09712, Lift coefficient of: 455.23564 , Drag force of : 244.44699N and Lift force of: 278.83183 N. Model 3 with a maximum Velocity of 59.8387 m/s and a maximum pressure of 1136.72 Pa, Drag coefficient of : 610,89875, Lift coefficient of: 764,99562, Drag force of: 374,17548 N and Lift force of: 468,55982 N. Based on results analysis using ansys software, Model 1 was chosen because it has the smallest Drag Coefficient, Lift Coefficient, Drag Force and Lift Force.